The effect of rehabilitation on remission following detoxification treatment in alcohol and substance use disorders: A pilot study - Mustafa Danisman; Gamze Zengin Ispir; Kubra Sezer Katar; Zehra Ucar Hasanli; Ziya Bilgin (Medicine Science)
Alcohol and substance use disorders (ASUD) are characterized by persistent substance use behavior despite their harmful effects, and they are chronic and recurrent disorders. In the treatment of ASUD, in addition to pharmacological treatment and the treatment of comorbid psychiatric disorders, the inclusion of rehabilitation in the treatment processes is also essential because of the high relapse rates after detoxification treatment. In our country, although the number of detoxification centers for ASUD has increased over the years, rehabilitation services have remained inadequate. This retrospective study aims to compare the remission periods of ASUD patients who received and did not receive rehabilitation services after completing their detoxification treatments in our clinic and to contribute to the literature in this field. In this study, we compared the remission periods of 33 patients who completed inpatient detoxification treatment in our clinic and then received inpatient rehabilitation services with 33 patients who did not receive rehabilitation services. The findings showed that patients who received rehabilitation treatment had longer remission periods. Rehabilitation services are of critical importance in combating addiction and need to be expanded in our country. [Med-Science 2024; 13(4.000): 840-6]